Type 2 Diabetes Elicits Lower Nitric Oxide, Bradykinin Concentration and Kallikrein Activity Together with Higher DesArg(9)-BK and Reduced Post-Exercise Hypotension Compared to Non-Diabetic Condition - Simoes, Herbert Gustavo (2013)
This study compared the plasma kallikrein activity (PKA), bradykinin concentration (BK), DesArg(9)-BK production, nitric oxide release (NO) and blood pressure (BP) response after moderate-intensity aerobic exercise performed by individuals with and without type 2 diabetes. Ten subjects with type 2 diabetes (T2D) and 10 without type 2 diabetes (ND) underwent three sessions: 1) maximal incremental test on cycle ergometer to determine lactate threshold (LT); 2) 20-min of constant-load exercise on cycle ergometer, at 90% LT and; 3) control session. BP and oxygen uptake were measured at rest and at 15, 30 and 45 min post-exercise. Venous blood samples were collected at 15 and 45 minutes of the recovery period for further analysis of PKA, BK and DesArg(9)-BK. Nitrite plus nitrate (NOx) was analyzed at 15 minutes post exercise. The ND group presented post-exercise hypotension (PEH) of systolic blood pressure and mean arterial pressure on the 90% LT session but T2D group did not. Plasma NOx increased similar to 24.4% for ND and similar to 13.8% for T2D group 15min after the exercise session. Additionally, only ND individuals showed increases in PKA and BK in response to exercise and only T2D group showed increased DesArg(9)-BK production. It was concluded that T2D individuals presented lower PKA, BK and NOx release as well as higher DesArg(9)-BK production and reduced PEH in relation to ND participants after a single exercise session.